LANGUAGE LEVERAGED MARKETING AND BUSINESS COMPETITIVENESS OF MULTINATIONAL SHIPPING COMPANIES IN PORT HARCOURT, NIGERIA - Aguocha, Chukwunonso Oscar; Eke, Haniel Okorafor (Scholars Digest Publishing, 2025)
The purpose of this study was to investigate whether or not international shipping companies in Port Harcourt benefit from language-based marketing strategies. In all, 72 shipping company workers were polled as part of the cross-sectional survey technique used in the study. In addition, the four hypotheses were tested using Spearman's Rank Correlation Coefficient, which showed that language-driven marketing significantly increased the competitiveness of MNCs in the Port Harcourt shipping industry. According to the research, international shipping companies in Port Harcourt can gain an advantage through language-driven marketing. The paper suggests that shipping company executives gauge the language needs and preferences of Port Harcourt's potential customers and other stakeholders through market research. Company executives in the shipping industry have a responsibility to ensure that all promotional materials, such as website copy, social media messages, and promotional goods, are translated into the local languages and dialects.
Keywords: Language Leveraged Marketing, Business Competitiveness, Artificial Intelligence Language.